The Oxford handbook of pragmatics - Huang, Yan, 1955- (Oxford University Press, 2017)
This volume brings together distinguished scholars from all over the world to present an authoritative, thorough, and yet accessible state-of-the-art survey of current issues in pragmatics. It covers a wide range of topics and will be an indispensable reference for scholars and students in pragmatics, philosophy of language, and related fields.- Resumé vydavatel
Keywords: pragmatika; pragmatics; elektronické knihy; příručky; electronic books; handbooks and manuals